Servant leadership and job satisfaction: The mediating role of trust and leader-member exchange - Dami, Zummy Anselmus; Imron, Ali; Burhanuddin, Burhanuddin; Supriyanto, Achmad (Frontiers in Education, 2022)
Objective The study aimed to examine the role of trust mediation and leader-member exchange in the influence of servant leadership on job satisfaction. Background Research on the relationship between servant leadership and academic job satisfaction is rare. The study of servant leadership in Christian higher education is dominated by non-research (conceptual), literature review, and church ministry, instrument development, verification, and validation, quantitative (pre- and post-test), quantitative (descriptive), and qualitative studies. Thus, there have been no studies that test and measure complex variables simultaneously in one model that includes servant leadership, trust (job-related outcomes + mediator), leader-member exchange (behavioral outcome), and job satisfaction (well-being + outcome) in the context of Christian higher education in Indonesia. Servant leadership still needs to be done in work-related outcomes such as trust variables. Research on academic job satisfaction in non-European and non-Western contexts is still dominant in Palestine. Finally, the placement of trust as a mediation variable needs to be more consistent because trust also has a role as a predictor of servant leadership. Method This study used quantitative methods with a sample of 160 lecturers from 26 Christian higher education in Indonesia. This study used the partial least square (PLS-SEM) approach to verify the proposed hypothesis. Results The results showed that servant leadership has a significant positive effect on job satisfaction and trust, and LMX mediate the influence of servant leadership on job satisfaction. Finally, trust and LMX are complementary mediation effects of servant leadership on job satisfaction. Conclusion Servant leadership increases trust, LMX and job satisfaction. Trust and LMX increase job satisfaction. Trust and LMX have a mediating role in the effect of servant leadership on job satisfaction. Implications Rectors/chairmen who engage in high-level interactions with lecturers will influence trust, reduce losses, and maximize gains in their interactional relationships. In addition, based on the theory of leader-member exchange, high-quality, trustworthy, and satisfactory leader-member exchange relationships positively affect the personal growth, work attitudes, and performance of lecturers. The Private Higher Education Organizing Body (BPPTS) needs to prepare for leadership regeneration by preparing future service leaders through training that directly supports the improvement of servant leadership behavior. This is important because servant leadership behavior becomes essential to increase trust, LMX and lecturer job satisfaction and achieve Christian higher education goals. Finally, Power distances, short-term orientation cultures, and paternalistic are not found to be obstacles to servant leadership practices in Indonesian Christian higher education.